Evaluation of inoculant and NPN silage additives: a summary of 26 trials and 65 farm-scale silages - K.K. Bolsen; R.N. Sonon; B. Dalke; Ronald V. Pope; Jack G. Riley; A. Laytimi (Kansas Agricultural Experiment Station Research Reports, 1992)
Results from 26 trials comparing fermentation, dry matter (DM) recovery, and effects on cattle performance of inoculated or nonprotein nitrogen (NPN)-treated silages vs. controls were summarized using paired t-test analysis. Inoculants consistently improved fermentation efficiency, DM recovery, feed conversion, and gain per ton of crop ensiled in both corn and forage sorghum silages. The use of NPN, particularly urea or anhydrous ammonia, adversely affected fermentation efficiency, DM recovery, avg daily gain, and gain per ton of crop ensiled, particularly for the higher moisture forage sorghums.
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Inoculant; Urea; Ammonia; Molasses; Silage